Dr Namrata TRUE TALES OF TEN T-PLL OVER A DECADE - Dr Namrata.N. Rajakumar; Dr Raghavendra .H. Vijaya; Dr laxmi B Horatti; Dr Girish Balikai; Dr Murugesh Shamnur (International Journal of Medical Research and Review, 2023)
BackgroundT- prolymphocytic leukemia(T-PLL) ,are aggressive lymphoid malignancies with unique morphologic, cytogenetic, immunophenotypic, and molecular features. T-PLL is a mature T-cell leukemia typically presenting at stages of exponentially rising lymphocyte counts in peripheral blood,accompanied by splenomegaly and bone marrow involvement. They are extremely rare  ,comprising of <2% of  mature T –leukemias and inherently aggressive and notoriously refractory to therapeutics.Extensive  search for Indian literature on T-PLL and  Immunophenotypic characterization of this entity did not yield any results. We analysed the characteristics, prognostic factors, outcomes and treatments of 10 patients with T-PLL . To our knowledge this is  the largest series of T-PLL from India , this study reviews clinical, cytogentic and flow cytometric immunophenotyping  findings, and differential diagnosis  of patients with T-cell prolymphocytic leukemia from January 2012 to January 2022.Methods: Our laboratory received 4500  clinically  suspected chronic leukemias, during a period of 10 years ,at kidwai memorial institute of oncology ,which is state cancer institute , where  diagnostic flow cytometric analysis was done and leukemias were classified based on WHO  2008 criterias.  Results: out of 4500 cases of Chronic lympho proliferative disorders sent for flow cytometric immunophenotyping, only 10 cases were  diagnosed as T-PLL .Study period January 2012 to January 2022.Conclusions: Evaluation of immunophenotype  of this  rare entity by flow cytometry is a critical     part of  diagnosis and is a indespensible tool in distinguishing T-PLL from other mature T-cell lymphoid   neoplasms.Awareness of this rare entity aids in work up .